PENGARUH MODEL WHOLE LANGUAGE TERHADAP KEMAMPUAN MEMBACA KREATIF TEKS DONGENG SISWA SEKOLAH DASAR - Pipit Puspitasari; Dudu Suhandi Saputra; Ari Yanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read with creative strategies is one of the most vital aspects of literacy for elementary school children, as it plays a role in honing their critical, imaginative, and interpretive thinking skills regarding reading materials. Teaching reading creatively with fairy tale texts requires strategies that actively engage students in understanding, interpreting, and connecting the content of the reading to their own experiences. One approach that can be used is the Whole Language model, which sees language as a whole in language activities. This research aims to assess the impact of the Whole Language model on creative reading abilities in fairy tale texts among elementary school students by applying the Systematic Literature Review (SLR) method. The data collection stage was conducted by searching for articles on Google Scholar published between 2020 and 2025. Selection based on inclusion criteria resulted in 13 articles that were just right for analysis. The study showed that the Whole Language model had a positive impact on reading ability, reading comprehension, literacy, literary appreciation, and student engagement in learning Indonesian. These findings suggest that the Whole Language model is a useful method for helping develop creative reading skills with fairy tale texts for elementary school students.